A Modular Class of Fluorescent Difluoroboranes: Synthesis, Structure, Optical Properties, Theoretical Calculations and Applications for Biological Imaging. Issue 35 (28th July 2016) - Bachollet, Sylvestre P. J. T.; Volz, Daniel; Fiser, Béla; Münch, Stephan; Rönicke, Franziska; Carrillo, Jokin; Adams, Harry; Schepers, Ute; Gómez‐Bengoa, Enrique; Bräse, Stefan; Harrity, Joseph P. A.
Abstract: Ten borylated bipyridines (BOBIPYs) have been synthesized and selected structural modifications have been made that allow useful structure–optical property relationships to be gathered. These systems have been further investigated using DFT calculations and spectroscopic measurements, showing blue to green fluorescence with quantum yields up to 41 %. They allow full mapping of the structure to determine where selected functionalities can be implemented, to tune the optical properties or to incorporate linking groups. The best derivative was thus functionalised with an alkyne linker, which would enable further applications through click chemistry and in this optic, the stability of the fluorophores has been evaluated. Abstract : Lighting the way : A family of borylated bipyridines (BOBIPYs) fluorophores offers tunable optical properties and linker possibilities via a designed strategy of synthesis. The photophysical properties of these compounds have been measured, and the results interrogated by DFT calculations, enabling the mapping of the structure for further implementations.